Influence of flow shallowness on scour depth at semi-integral bridge piers - Akib, Shatirah; Othman, Faridah; Sholichin, Mohammad; Fayyadh, Moatasem M.; Shirazi, S.M.; Primasari, Budhi (2011)
The paper presents the experimental study on the effect of flow shallowness on the scouring at semi-integral bridge piers. The experimental work was conducted in the Hydraulic Laboratory of University of Malaya. Out of 1020 data collected in the flow shallowness and time evolution experiments, 60 data were chosen at maximum scour depth to be analyzed. 30 data for sediment size of dso = 0.8 mm and 30 data for dso = 0.26 mm were taken at each side of the piers. The results showed that similar trend was produced for both sediment sizes, the depth of scour increased with the flow depth. Almost all of the data plotted gave the best correlation coefficient. The scour depth at the left and right side of the pier were almost averaged.